Implementasi Lean Thinking Pada Strategi Perbaikan Alur Pelayanan Farmasi Rawat Jalan (Studi Kasus di RS Primaya Depok) - Cinthya Margaretha, Sarah; Yaniawati, Poppy; Veranita, Mira (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2024)
A professional hospital service flow is required so that it can be carried out well and by the wishes of health service users by prioritizing patient safety and service quality. One of the service lines in hospitals is outpatient pharmacy services. Primaya Hospital Depok has outpatient pharmacy services with visits that continue to increase every year and many complaints regarding outpatient services which become obstacles to the flow of outpatient care. This research uses qualitative methods in the form of interviews and observations using the concept of lean thinking. The results show findings in the form of waste Defects, overproduction, waiting, transportation, inventory, Motion and excess processing. The longest process and the most waste Waitingis found, namely Waitingfor the entire outpatient pharmacy service process. Suggestions for short-term improvements are given in the form of providing direction and warnings to officers so that they do not have to repeat work, making instructional banners as well as service flow and implementing 5S. The long-term improvement proposal provided is in the form of improving the flow of outpatient services by taking into account the reduction of waste found.